2021
DOI: 10.3390/ijerph18041552
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Styles and Nurses’ Job Satisfaction. Results of a Systematic Review

Abstract: Healthcare organisations are social systems in which human resources are the most important factor. Leadership plays a key role, affecting outcomes for professionals, patients and work environment. The aim of this research was to identify and analyse the knowledge present to date concerning the correlation between leadership styles and nurses’ job satisfaction. A systematic review was carried out on PubMed, CINAHL and Embase using the following inclusion criteria: impact of different leadership styles on nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 36 publications
6
111
1
2
Order By: Relevance
“…25 A previous study indicates limitation in the educational opportunity as one of the factors limiting extrinsic job satisfaction. 26 Overall, the level of job satisfaction in the current study was lower than those reported in Lebanon 8 and higher than those reported in Egypt. 15 The differences in job satisfaction levels observed in the current study and previous studies might be due to differences in methodology adopted and instruments used.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…25 A previous study indicates limitation in the educational opportunity as one of the factors limiting extrinsic job satisfaction. 26 Overall, the level of job satisfaction in the current study was lower than those reported in Lebanon 8 and higher than those reported in Egypt. 15 The differences in job satisfaction levels observed in the current study and previous studies might be due to differences in methodology adopted and instruments used.…”
Section: Discussioncontrasting
confidence: 67%
“…It is also evident that supervisory behavior influences job satisfaction of an employees by impacting their morality and work behavior, 11 psychological well-being, 28 and by the way of empowerment. 26 The findings of the study should be interpreted in the light of its limitations. It is probable that there might be reporting bias since data collection was carried out using a self-reported questionnaire.…”
Section: Discussionmentioning
confidence: 96%
“…Concerning the prevalence of different styles (first study objective), literature indicated that teamwork, sometimes known as the participative style, was more frequently practiced than the other two coexisting styles, namely the autocratic and laissez-faire (Specchia et al, 2021;Akparep, Jengre & Mogre, 2019;Yao, Woan, Li & Ahmad, 2017). Some studies such as Munir and Iqbal (2018) did not only report teamwork as the most practiced style, but also graded the other two in terms of the dictatorial style coming next, and the indifferent being third -but 'hardly practiced'.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A later review of the literature from 2017, building mainly on data on nurses, managers and patients, also identified the significance of leadership styles and practices on patient outcomes, health care workforce and organisational culture, with leadership styles that reflected a collaborative, multifaceted and dynamic process (e.g., transformational, employee-oriented leadership) being more effective and promoting positive outcomes [ 52 ]. The most recent systematic review on leadership styles and nurses’ job satisfaction from 2021 confirmed this picture [ 53 ].…”
Section: Introductionmentioning
confidence: 99%